Recent Progress in FD-LC-MS/MS Proteomics Method - Kobayashi, Hiroshi; Imai, Kazuhiro (Frontiers in Chemistry, 2021)
In the course of our studies on Bio-Analytical Chemistry, a novel proteomics analysis method, FD-LC-MS/MS (fluorogenic derivatization-liquid chromatography-tandem mass spectrometry) proteomics method, has been developed. It consists of fluorogenic derivatization (FD), LC separation and detection/quantification of the derivatized proteins, followed by isolation, tryptic digestion of the isolated proteins, and final identification of the isolated proteins using electrospray ionization nano-LC-MS/MS of the generated peptides mixture with probability-based proteins identification algorithm. The method was applicable to proteomics finger print analysis of individual cells to recognize human cells. It is also suitable for differential proteomics analysis: The different 2 biological samples are treated in the same manner as described above such as derivatization and etc., the 2 chromatograms obtained are compared one by one with finding protein peaks having different peak heights (fluctuated proteins) between the 2 chromatograms, isolating the peak fractions and identifying the altered proteins between the two samples. Thus, various biological samples, such as human cancer cell lines, demonstrating several biomarkers for cancers and the liver of a hepatitis-infected model mouse. For more efficient separation, a nano-flow LC with a phenyl-bonded monolithic silica-based capillary column was adopted for cell-expressed intact protein analysis. The derivatized human cell proteins (K562) and yeast cell (Saccharomyces cerevisiae) proteins as model intact cell proteins were subjected to this nano-flow LC with florescence detection. More than 1,300 protein peaks were separated/detected from both cells. Then, for straightforward comparison of multiple peak separation profiles, a novel kind of chromatogram display, dubbed the “spiderweb” chromatogram, is proposed. A trial of nano-LC-FD-LC-mass spectrometry for molecular weight estimation of FD-proteins is also conducted.